2007
DOI: 10.1115/1.2746395
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Cold Bends for Line Pipes

Abstract: To comprehensively investigate the tensile properties of cold bends, full-scale cold bending experiments, tensile tests using prestrained small-scale specimens, and finite element (FE) analyses of the cold bending processes were conducted on API 5L X60 and X80 grade line pipes. The tensile tests revealed that the tensile properties of the cold bends were comparable to the uniaxially prestrained specimens machined from the straight part of the pipes. A FE model simulating the cold bending process was verified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…By contrast, a very limited knowledge has been established about the changes in the creep strength and high-temperature behaviour of hot bent thick-walled pipes [13][14][15][16][17][18]. The common basic topics in the analyses of bending characteristics have been addressed such as wrinkling instability, over thinning, cross-section deformation and springback phenomenon.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By contrast, a very limited knowledge has been established about the changes in the creep strength and high-temperature behaviour of hot bent thick-walled pipes [13][14][15][16][17][18]. The common basic topics in the analyses of bending characteristics have been addressed such as wrinkling instability, over thinning, cross-section deformation and springback phenomenon.…”
Section: Introductionmentioning
confidence: 98%
“…The tungsten-modified 9%Cr steel P92 (ASTM Grade P92) was introduced in plants in 2001 [3]. Much effort has been applied to investigating the effects of cold bending on thin-walled pipes for line pipe applications [12][13][14]. It was reported that the tensile properties of the cold bends are different from those of the straight pipes due to work hardening and the Bauschinger effect [12].…”
Section: Introductionmentioning
confidence: 98%